SOCAL-10 planning meeting--notes and summary - Southall, Brandon L. (Monterey, California. Naval Postgraduate School, 2010)
Minutes and notes from the planning meeting for the Southern California SOCAL-10 Marine Mammal monitoring and research experiment are presented. A summary of the outcomes/conclusions from that meeting follows. General topics discussed were on which animals to focus primarily (and secondarily) for this experiment and the mechanics of studying those animals for this experiment (e.g., the type of tags to use, the vessels to be used, sound source specifications and usage, coordination with other monitoring/research efforts, etc.). The tentative timing of the experiment was discussed. Future plans/ideas for subsequent experiments--SOCAL-11 and beyond--were also discussed.